Single-cell RNA sequencing uncovers molecular mechanisms of intravenous immunoglobulin plus methylprednisolone in Kawasaki disease: attenuated monocyte-driven inflammation and improved NK cell cytotoxicity - Yang, Minna; Chen, Yeshi; Feng, Chenhui; Zhang, Mingming; Wang, Hongmao; Zheng, Yang; Li, Xiaohui (Frontiers in Immunology, 2024)
Intravenous immunoglobulin (IVIG) plus methylprednisolone as initial intensive therapy or additional therapy in Kawasaki disease (KD) has been used in clinical practice. However, its molecular and cellular mechanism is unclear. We performed single-cell analysis on 14 peripheral blood mononuclear cell (PBMC) samples obtained from 7 KD patients who received either IVIG monotherapy or IVIG plus methylprednisolone therapy. This encompassed 4 samples from KD patients collected before and after IVIG treatment, as well as 3 samples from KD patients before and after IVIG plus methylprednisolone therapy. Both IVIG monotherapy and IVIG plus methylprednisolone therapy can increase lymphocyte counts (e.g. CD4+T, CD8+T, and γδT cells) to address lymphopenia. They can also decrease monocyte counts and repress the expression of S100A12, NLRP3, and genes associated with immune-cell migration in monocytes. IVIG combined with methylprednisolone downregulates more monocyte-driven inflammatory pathways than IVIG alone. Additionally, this combination uniquely enhances NK cell cytotoxicity by modulating receptor homeostasis, while significantly upregulating interferon-related genes in CD4+ T cells, CD8+ T cells, and B cells, particularly type I interferons. In conclusion, the combination of IVIG with methylprednisolone attenuated monocyte-driven inflammation and improved NK cell cytotoxicity which might provide clues for pediatricians to consider treatment options for children with KD. Whether the monocytedriven hyperinflammatory state and NK cell function can be indicators for the clinical choice of IVIG with methylprednisolone therapy in KD needs further investigation.